PENATALAKSANAAN FISIOTERAPI KASUS ATELEKTASIS PADA ANAK CEREBAL PALSY DENGAN MODALITAS IR, CHEST THERAPI DAN METODE NDT DI YPAC SURAKARTA - Lusiani Arum Fadhilah; Nur Susanti (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2017)
Atelectasis is one of the complications of cerbral palsy, this is because children with CP condition almost all have low levels of activity than children usually. If the activity of motion is low, the body does not move optimally thorax cage is difficult to inflate and deflate fully and relax. Factors that affect the occurrence of atelectasis are among other abnormalities during pregnancy, CMV viral infection. Problematic atelectasis in atelectasis in children hypothonic spiral hypothonic spastic athetoid quadriplegi type of flexion is respiratory muscle spasms, shortness of breath, decreased thorax expansion, sensory disturbance with, reflex disorders, functional activity. Physiotherapy modalities that can be given in this condition is by giving the modality of infrared, chest therapi, and neuro development treatment. The conclusion is that using physiotherapy interventions with IR, therapeutic chest, and NDT may help reduce the problems that arise in the condition of atelectasis in children with cerebral palsy.